2019
DOI: 10.14743/apem2019.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser helical drilling of nickel-base single-crystal super-alloy: Effect of machining parameters on geometrical characteristics of micro-holes

Abstract: Laser micro-hole processing has been widely used in industry. Many laser processing parameters can affect the processing results. The relationship between the geometrical shapes of micro-holes and the laser processing parameters has not been determined accurately. In this paper, experiments on the femtosecond laser drilling of the nickel-base single-crystal super-alloy (DD6) materials were conducted to determine the relationship between the parameters, such as the laser single-pulse energy, rotation rate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At the University of Stuttgart, Germany, physical experiments on annular drilling were conducted based on a four-light wedge rotation system, demonstrating that the quality achieved by annular drilling was significantly improved compared to that by percussion drilling [24]. Yin et al [25] found that femtosecond laser spiral machining can better handle high depth-to-diameter ratio holes, but the relationship between the geometric evolution process of small hole formation and the main processing parameters during spiral hole making is unclear. Moreover, there is a lack of model guidance for the optimization of processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…At the University of Stuttgart, Germany, physical experiments on annular drilling were conducted based on a four-light wedge rotation system, demonstrating that the quality achieved by annular drilling was significantly improved compared to that by percussion drilling [24]. Yin et al [25] found that femtosecond laser spiral machining can better handle high depth-to-diameter ratio holes, but the relationship between the geometric evolution process of small hole formation and the main processing parameters during spiral hole making is unclear. Moreover, there is a lack of model guidance for the optimization of processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of current femtosecond laser parameters on single-crystal high-temperature alloys has been studied by scholars to some extent. It has been shown that the diameter increases with increasing single pulse energy in the range of 80 µJ to 130 µJ [12]. The entrance and exit diameters and roundness tend to be stable, while the taper exhibits a slight variation.…”
Section: Introductionmentioning
confidence: 99%